Breaking boundaries: female biblical interpreters who challenged the status quo - Calvert-Koyzis, Nancy; Weir, Heather E. (Library of Hebrew bible/Old Testament studies, 2010)
Women throughout the centuries have sought to break out of the constraints that their societies deemed appropriate for them. For interpreters in the Christian tradition, this often meant examining biblical texts that had been understood in ways that demeaned women